A systematic optimization technique for the coefficient of thermal expansion of Portland cement concrete. (30th July 2015) - Siddiqui, Md Sarwar; Fowler, David W.
Highlights: First systematic approach to optimize concrete CTE. CTE can be reduced by replacing high-CTE aggregates with low-CTE aggregates. CTE can be reduced by reducing cement paste volume. A step-by-step concrete CTE optimization technique. Abstract: The coefficient of thermal expansion (CTE) of concrete is one of the important concrete properties that is responsible for the deterioration of concrete pavements and structures. A significant savings in repair and rehabilitation cost can be achieved by optimizing the CTE of concrete according to the need of the concrete pavements and structures. CTE reduction also improves the durability and longevity. CTE of concrete is dependent on the CTE of its constituents. Replacing high-CTE aggregates with low-CTE aggregates can significantly reduce the CTE of overall concrete. In addition, concrete CTE can be reduced by reducing the cement paste volume. This study presented systematic guideline to select the concrete constituents to achieve a target CTE.